Five dimensions of quality : a common sense guide to accreditation and accountability - Suskie, Linda A. (Jossey-Bass, A Wiley Brand, 2014)
"Meet calls for increased quality and understand accreditation expectationsAuthor Linda Suskie is internationally recognized for her work in higher education assessment, and she is a former vice president of a major regional accreditor. In Five Dimensions of Quality: A Common Sense Guide to Accreditation and Accountability in Higher Education she provides a simple, straightforward model for understanding and meeting the calls for increased quality in higher education ever-present in today's culture. Whether your institution is seeking accreditation or not, the five dimensions she outlines will help you to identify ways to improve institutional quality and demonstrate that quality to constituents. For those wading through the accreditation process, which has become more difficult in recent years due to increasing regulation and pressure for greater accountability, Suskie offers expert guidance on understanding the underlying principles of the expectations of accrediting bodies. Using the model presented here, which is much easier to understand than the sometimes complex resources provided by individual accrediting bodies, American colleges and universities can understand what they need to do to earn and maintain their regional accreditation as well as improve overall institutional quality for their students. You'll be able to: Identify ways to improve institutional quality Demonstrate the quality of your institution to internal and external constituents Avoid wasting time and energy on misguided institutional processes to comply with accreditation requirements By focusing on why colleges and universities should take particular actions rather than only on what those actions should be, Five Dimensions of Quality gives them the knowledge and strategies to prepare for a successful review. It is an ideal resource for leaders, accreditation committee members, and everyone on campus"- Resumé vydavatel
Keywords: pedagogická evaluace; vysokoškolské studium; akreditace; educational evaluation; college study; accreditation; elektronické knihy; monografie; electronic books; monographs